Intelligent Systems Design and Applications 2003
DOI: 10.1007/978-3-540-44999-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface Residues Involved in Protein-Protein Interaction — A Support Vector Machine Approach

Abstract: SummaryWe describe a machine learning approach for sequence-based prediction of protein-protein interaction sites. A support vector machine (SVM) classifier was trained to predict whether or not a surface residue is an interface residue (i.e., is located in the protein-protein interaction surface) based on the identity of the target residue and its 10 sequence neighbors. Separate classifiers were trained on proteins from two categories of complexes, antibody-antigen and proteaseinhibitor. The effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
1
30
1
Order By: Relevance
“…The present approach achieves a substantial improvement of the prediction accuracy from 2.2% to 8.2% on a dataset of 77 individulal proteins collected from the Protein Data Bank compared to the previously reported best prediction accuracies with SVM methods [5,9]. Results of our experiments with the proposed encoding schema confirmed that the accessible surface areas and the evolutionary information of amino acids along the sequences can detect different sequence features to enhance the accuracy of protein-protein interaction residue prediction.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present approach achieves a substantial improvement of the prediction accuracy from 2.2% to 8.2% on a dataset of 77 individulal proteins collected from the Protein Data Bank compared to the previously reported best prediction accuracies with SVM methods [5,9]. Results of our experiments with the proposed encoding schema confirmed that the accessible surface areas and the evolutionary information of amino acids along the sequences can detect different sequence features to enhance the accuracy of protein-protein interaction residue prediction.…”
Section: Introductionsupporting
confidence: 82%
“…Chen and Zhou introduced a consensus neural network that combines predictions from multiple models with different levels of accuracy and coverage [4]. Input information derived from single sequences has been used by support vector machine (SVM) for predicting protein-protein interface residues [9]. Recently, Yan et al proposed a two-stage classifier consisting of an SVM and a Bayesian network classifier that identifies interface residues primarily on the basis of sequence information [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess our method objectively, two indices, i.e., specificity and sensitivity (Baldi et al, 2000;Yan and Dobbs, 2003;Wang et al, 2006), are introduced in this paper.…”
Section: Evaluation Measures For Performance Of Predictorsmentioning
confidence: 99%
“…• Learning AVT from data for a broad range of real world applications such as census data analysis, text classification, intrusion detection from system log data [13], learning classifiers from relational data [2], and protein function classification [25] and identification of protein-protein interfaces [27].…”
Section: Future Workmentioning
confidence: 99%